Kearifan Lokal Dalam Pengeloaan Ekosistem Hutan Mangrove : Studi Kasus Di Gonda Mangrove Park Kecamatan Campalagian Kabupaten Polewali Mandar - Syarmilah; Carong, Suparjo Razasli; Makmur; Qaizar (Program Studi Kehutanan Fakultas Pertanian dan Kehutanan Universitas Sulawesi Barat, 2022)
Realizing the importance of the necessities of life that come from natural resources, a solution is needed to combine ecological and economic aspects to that they cas work together and in balance. Local wisdom plays a role in managing the natural resources of the environment. This study aims to determine local wisdom in the management of mangrove forest ecosystems in Gonda Mangrove Park, Campalagian District, Polewali Mandar Regency. This research was conducted from May to June 2021. The method used in this research is a qualitative descriptive method using observation data colletion techniques, interviews using interview guides, and documentation. The result of the research show that local community wisdom in the management of mangrove forest ecosystem in Gonda includes: Diposara’ mappaleo’ and there are mystical stories of the community, as well as the use of mangrove forest products by the community such as the use of Salaq’-salaq’ (Bruguiera gymnorhiza) and Lawo-lawo (Xylocarpus granatum) fruit.